Biochemical and functional properties of vesicles from planktonic and biofilm phenotypes of Limosilactobacillus reuteri DSM 17938 - Beatrice Marinacci; Chiara D’Ambrosio; Irene Vitale; Antonella Di Sotto; Francesco Cairone; Mattia Spano; Simone Carradori; Andrea Scaloni; Marco Gullì; Valentina Puca; Santolo Francati; Monica Matuozzo; et al. (Scientific Reports)
Abstract Limosilactobacillus reuteri DSM 17938 is among the world’s most studied probiotic strains and has been shown to provide several health benefits for the host. We have previously shown that the cell-free supernatant of L. reuteri DSM 17938 possesses antimicrobial activity and contains several bioactive compounds. Furthermore, the strain was shown to be a biofilm producer that releases both planktonic and biofilm Membrane Vesicles (MVs). In this study, membrane vesicles isolated from planktonic (pMVs) and biofilm (bMVs) phenotypes were comparatively investigated for their toxicity, ability to kill cancer as well as non-cancer cell lines and modulate phagocytosis in murine macrophages. Neither pMVs nor bMVs showed any in vivo toxicity in a Galleria mellonella model, and weakly affected cancer and noncancerous cell viability after both short- and long-term treatments. However, they were able to affect phagocytosis in lipopolysaccharide challenged RAW 264.7 macrophages, suggesting possible immunomodulatory properties. NMR-based metabolomic analysis of pMVs and bMVs identified and quantified engulfed compounds, mainly organic acids and amino acids, with lactate being the most abundant molecule in both vesicle types. bMVs contained higher concentrations of all measured metabolites compared to pMVs. Proteomic analysis of pMVs and bMVs described equivalent protein cargos, emphasizing quantitative compositional differences that presumably reflect the physiological state of each parent bacterial phenotype. Through the assignment of molecules possibly acting as mediators of immune/inflammatory responses in the host and/or modulating known beneficial effects of L. reuteri, important signaling functions of these vesicles were suggested. Finally, storage stability of MVs up to four weeks was established.